2014
DOI: 10.1007/s00277-014-2126-9
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine in 302 patients with WHO-defined acute myeloid leukemia: results from the Austrian Azacitidine Registry of the AGMT-Study Group

Abstract: Data on efficacy and safety of azacitidine in acute myeloid leukemia (AML) with >30 % bone marrow (BM) blasts are limited, and the drug can only be used off-label in these patients. We previously reported on the efficacy and safety of azacitidine in 155 AML patients treated within the Austrian Azacitidine Registry (clinicaltrials.gov identifier NCT01595295). We herein update this report with a population almost twice as large (n = 302). This cohort included 172 patients with >30 % BM blasts; 93 % would have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
86
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 26 publications
6
86
1
4
Order By: Relevance
“…In total 7 patients with MDS or CMML and 2 patients with AML receiving CC‐486 monotherapy in this study attained CR or PR, including, importantly, patients for whom previous DNMTi therapy had failed. While multiple studies have shown injectable azacitidine can improve OS in higher‐risk MDS and AML without requiring CR5, 7, 8, 9, 37; the effect of CC‐486 on OS has not yet been reported and was not captured in this phase 1 study, but is under investigation in an ongoing phase 3 trial of CC‐486 in patients with MDS (NCT01566695).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In total 7 patients with MDS or CMML and 2 patients with AML receiving CC‐486 monotherapy in this study attained CR or PR, including, importantly, patients for whom previous DNMTi therapy had failed. While multiple studies have shown injectable azacitidine can improve OS in higher‐risk MDS and AML without requiring CR5, 7, 8, 9, 37; the effect of CC‐486 on OS has not yet been reported and was not captured in this phase 1 study, but is under investigation in an ongoing phase 3 trial of CC‐486 in patients with MDS (NCT01566695).…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral azacitidine has been extensively evaluated in patients with MDS, chronic myelomonocytic leukemia (CMML), and AML in large randomized clinical trials,5, 6, 7 in regional registry studies,8, 9, 10, 11, 12, 13 and in numerous smaller retrospective analyses of patients treated in community practice 14, 15. These studies show azacitidine reduces cytopenias in select lower‐risk MDS and prolongs overall survival (OS) in higher‐risk MDS and AML,5, 6, 7, 16 may be effective maintenance therapy after induction chemotherapy (IC) or allogeneic hematopoietic stem cell transplant (alloHSCT),17, 18, 19, 20 and can induce responses in patients with relapsed/refractory disease 12, 21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest azacytidine studies describe either a similar overall survival of MDS patients with CK+/MK+ or CK+/MK− [30] or a worse outcome of AML patients with CK+/MK+ compared to CK+/MK− [31], albeit with limited patient numbers. Our post hoc analysis constitutes the first analysis of a phase III randomized HMA trial in MDS/ AML, but it has similar limitations: when comparing cytogenetic subgroups of DAC-treated patients, the numbers (particularly in the CK+/MK− group, n=9) became too small to allow meaningful comparisons of outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 302 patients were evaluated. The overall response rate was 48 %, and the median overall survival was 9.6 months [14].…”
Section: Discussionmentioning
confidence: 98%